1981
DOI: 10.4319/lo.1981.26.4.0697
|View full text |Cite
|
Sign up to set email alerts
|

Summer population fluctuations, feeding, and growth of Hydra in an arctic lake1

Abstract: During 1977, the population

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 5 publications
0
27
1
Order By: Relevance
“…Feeding rates are particularly important in regulating Hydra population densities. Laboratory studies have shown that Hydra population growth rates are directly related to frequency of feeding (Muscatine and Lenhoff, 1965;Otto and Campbell, 1977) and in the field, Hydra population densities were shown to closely follow increases in zooplankton abundance (Cuker and Mozley, 1981). The feeding process is divided into a series of discrete steps: capture of prey with nematocysts, transport of prey to mouth, mouth opening, ingestion, digestion and ejection of exoskeleton.…”
Section: Feedingmentioning
confidence: 99%
“…Feeding rates are particularly important in regulating Hydra population densities. Laboratory studies have shown that Hydra population growth rates are directly related to frequency of feeding (Muscatine and Lenhoff, 1965;Otto and Campbell, 1977) and in the field, Hydra population densities were shown to closely follow increases in zooplankton abundance (Cuker and Mozley, 1981). The feeding process is divided into a series of discrete steps: capture of prey with nematocysts, transport of prey to mouth, mouth opening, ingestion, digestion and ejection of exoskeleton.…”
Section: Feedingmentioning
confidence: 99%
“…in the summer. Some authors found that Hydra prefer smaller size prey, such as the representatives of Bosmina genus (Dodds and Cole, 2007) or Cyclops (Cuker and Mozley, 1981). Hydra species are classified as valuable study organisms, especially as predatory invertebrates in trophic relations, studied also in matter and energy transport through various macrophyte species in the lake ecosystem which support a diverse composition and abundance of invertebrate fauna, depending on the morphology of leaves, production of allelopathic compounds and depending on whether they are submerged, floating or emerged plants (Cheruvelil et al, 2002;Mc Abendroth, 2005;Bogut et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that hydras are preyed by platyelminthes (Hyman 1940, Kanaev 1969, despite the observation that small platyhelminths avoid contact with these cnidarians (Slobodkin & Bossert 2001). Cuker & Mozley (1981) It was apparent that the gastropods covered the hydras with mucus, thereby protecting themselves from the nematocysts. Therefore, the presence of nematocysts most likely prevented the consumption of hydras in the present study.…”
Section: Discussionmentioning
confidence: 99%